Comigo ninguém pode: a voz e o lugar de Regina Vater - Arethusa Almeida de Paula (2014)
This thesis intends to present the career of Regina Vater, a Brazilian artist. This in turn, is accomplished through an analysis of interviews and of her personal art collection. Additionally, it purports to provide an analysis juxtaposing the concept of her memory objects with a critical and theoretical view of her art work. Based on the granted access to her collection, sources are taken into account as well as documents, art objects and signifying elements, which give meaning to the art work presented. The structural hypothesis of this research is based on the thesis that, in this particular space, as the artist gathers and organizes her own trajectory, she also sheds light in ways of managing her own art work. This study also aims to restore the relevance of Regina Valters art work within the national art scene. With regards to Guy Bretts considerations, we believe the lengthy recognition of Regina Valters art work by the Brazilian art circuit is mainly due to a wide diversity in the media, formats and technologies encompassed by Regina Valters art production. It is noted that the artist work is mainly grounded on experimentation, conceptual idea and processes of art production. Driven by these concerns and supported by the granted access to the artist collection, the thesis seeks to elucidate pertinent questions in the realm of an unstable Contemporary Art field, such as: Is it possible to observe the artist performance through her art collection despite slightest historical distance in the context of a specific generation? Are strategies and conceptual framework identifiable under which her art production revolves around? How can boundaries be set with regards to access to the artist collection and/or work of relevance? There is no way to dismiss the character of intimacy generated by the contact with the artist in this study. Influenced by Regina Valters work and words, this thesis aims to signal the contribution of her work to the Brazilian art scene, and hence give voice to Regina Valter herself.